Pembuatan sistem interface digital untuk display data getaran dua dimensi dengan sensor fluxgate ( Making of a digital interface system for displaying two-dimensional vibration data with a fluxgate sensor) - Zulpadrianto Zulpadrianto; - Yulkifli; - Yohandri (PILLAR OF PHYSICS, 2015)
In this article will be discussed about data interface of  two-dimensional vibration detection using fluxgate sensors. Making the interface uses two programs are the program MPLAB X IDE V1.70 and Visual Basic programs in C #. MPLAB X IDE V1.70 program is used to program the analog data into digital data and program the data to be able to be connected via USB to a personal computer. Using the Visual Basic programming language C # aims to display digital data on personal computer in real time graphical form and the data stored in the xls extension. This research is a laboratory experiment. Data interface results will be displayed in the form of a graph consisting  of  vibration detection by fluxgate sensor vertically and horizontally. Extension xls stores data in excel format with the data stored in the form of the maximum scale and the delivery time of data from the vibration detection by fluxgate sensor. The personal computer interface signals for analog data that has been converted into digital data in PIC 18F4550 microcontroller